The habitat use of longsnout seahorse Hippocampus reidi in a subtropical Brazilian estuary - Julia Maria Maccari; Johnatas Adelir-Alves; Natalie Villar Freret-Meurer; Pedro Carlos Pinheiro (Neotropical Ichthyology)
Abstract Babitonga Bay, the largest estuary of Santa Catarina state, Brazil, is under intense environmental degradation, and the ecosystems (e.g., mangrove) and biodiversity (e.g., fish) are at risk. The longsnout seahorse Hippocampus reidi is avulnerablefish species found along the estuary, and this study aimed to compare the density and habitat use of longsnout seahorse in two different ecosystem structures along the Linguado Channel (southern mouth): one area with natural mangroves and another where mangroves were replaced by man-made structures. Data sampling was conducted biweekly for six months, from December 2021 to May 2022, during periods of ebb tide and low tide. Samples were collected by freediving along fixed transects, counting seahorses and recording pregnancy stage, behavior, and abiotic factors (salinity, temperature, precipitation, and pH). Salinity, temperature, precipitation and pH did not vary significantly over the months. Precipitation appeared to influence density in March. The results showed that both sampling areas had similarly low seahorse densities, but the sex ratio and number of pregnant males differed between the two sites. A male-biased sex ratio was observed throughout the study. Longsnout seahorses were frequently observed resting (anchored). These results offer valuable baseline data for future seahorse population assessments in Babitonga Bay.